Intravenous Immunoglobulin Use in Hemolytic Disease Due to ABO Incompatibility to Prevent Exchange Transfusion - Okulu, Emel; Erdeve, Omer; Kilic, Ilknur; Olukman, Ozgur; Calkavur, Sebnem; Buyukkale, Gokhan; Cetinkaya, Merih; Ulubas, Dilek; Demirel, Nihal; Hanta, Deniz; Ertugrul, Sabahattin; Gultekin, Nazli Dilay; et al. (Frontiers in Pediatrics, 2022)
Introduction: Intravenous immunoglobulin (IVIG) has been widely used to treat hemolytic disease of the newborn (HDN). Although it has been shown that IVIG treatment reduces the duration of phototherapy and hospitalization, the use of IVIG in hemolytic disease due to ABO incompatibility has been controversial in recent years. The aim of this study was to investigate the role of IVIG in the prevention of exchange transfusion in infants with ABO HDN who presented with bilirubin levels at or above the level of exchange transfusion. Materials and Methods: This study evaluated the data of infants with ABO HDN in the Turkish Neonatal Jaundice Online Registry. The infants with ABO HDN who met the total serum bilirubin level inclusion criteria (within 2–3 mg/dL of exchange transfusion or even above exchange transfusion level) were included in the study according to the guidelines from the American Academy of Pediatrics and the Turkish Neonatal Society. All patients were managed according to the unit protocols recommended by these guidelines, and received light-emitting diode (LED) phototherapy. Infants who only received LED phototherapy, and who received one dose of IVIG with LED phototherapy were compared. Results: During the study period, 531 term infants were included in the study according to inclusion criteria. There were 408 cases in the phototherapy only group, and 123 cases in the IVIG group. The demographic findings and the mean bilirubin and reticulocyte levels at admission were similar between the groups (p>0.05), whereas the mean hemoglobin level was slightly lower in the IVIG group (p=0.037). The mean age at admission was earlier, the need for exchange transfusion was higher, and the duration of phototherapy was longer in the IVIG group (p<0.001, p=0.001, and p<0.001, respectively). The rate of rehospitalization and acute bilirubin encephalopathy (ABE) was higher in the IVIG group (p<0.001, and p=0.01, respectively). Conclusion: In this study, we determined that one dose of IVIG did not prevent an exchange transfusion nor decrease the duration of phototherapy in infants with hemolytic disease due to ABO incompatibility who had bilirubin levels near or at exchange transfusion level.